Habitual Method in Moral Education of Grade 5 Students of KMI Darussalam Gontor Modern Islamic Institution - Hibatul Wafi; Ahmad Saifulloh (At-Ta'dib, 2019)
The world of education especially in terms of morals and akhlak in educational institutions shows moral degeneracy of students. This is indicated by the existence of actions that are not in accordance with the personality of a student such as brawls, drinking liquor, gambling, smoking and so forth. These deeds are not in accordance with the teachings of the Qur'an and as-Sunnah which are manifested in Law Number 20 of 2003 by the National Education System, Article number 3. In achieving the goals of Moral Education, efficient processes and methods are needed so that these objectives can be achieved maximally as desired. Therefore, Pondok Modern Darussalam Gontor is one of the Islamic education institutions in Ponorogo that conducts the process of education and teaching and learning by instilling Moral Education values to their students (santri). The purpose of this study was to determine the application of habituation methods in the moral education of fifth-grade students of KMI Pondok Modern Darussalam Gontor, as well as to know the supporting factors and inhibiting factors in their application. While the method used in this study is a qualitative descriptive study. To collect data, researchers used three methods, namely: interviews, observations, and documentaries, while in analyzing data, researchers used Miles and Huberman's theory which included three steps, namely: data collection, data reduction, data presentation, and conclusions.